2010
DOI: 10.1021/jo100286r
|View full text |Cite
|
Sign up to set email alerts
|

N-Heterocyclic Donor- and Acceptor-Type Ligands Based on 2-(1H-[1,2,3]Triazol-4-yl)pyridines and Their Ruthenium(II) Complexes

Abstract: New 2-(1H-[1,2,3]triazol-4-yl)pyridine bidentate ligands were synthesized as bipyridine analogs, whereas different phenylacetylene moieties of donor and acceptor nature were attached at the 5-position of the pyridine unit. The latter moieties featured a crucial influence on the electronic properties of those ligands. The N-heterocyclic ligands were coordinated to ruthenium(II) metal ions by using a bis(4,4'-dimethyl-2,2'-bipyridine)ruthenium(II) precursor. The donor or acceptor capability of the 2-(1H-[1,2,3]t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 48 publications
2
35
0
Order By: Relevance
“…In general, it is only the experimental UV absorption spectrum or emission energies that are compared with the theory. Our work on Ru, [197][198][199][200] Ir, [201,202] Pt [203,204] and Zn [205] complexes, and that of many other groups, see for example refs. [206][207][208][209], have found that, astonishingly, TD-DFT can be in reasonable agreement with the experiment as long as a judicious selection of functionals/basis is done and solvent effects are included.…”
Section: Excited-state Description Of Transition Metal Complexesmentioning
confidence: 94%
See 1 more Smart Citation
“…In general, it is only the experimental UV absorption spectrum or emission energies that are compared with the theory. Our work on Ru, [197][198][199][200] Ir, [201,202] Pt [203,204] and Zn [205] complexes, and that of many other groups, see for example refs. [206][207][208][209], have found that, astonishingly, TD-DFT can be in reasonable agreement with the experiment as long as a judicious selection of functionals/basis is done and solvent effects are included.…”
Section: Excited-state Description Of Transition Metal Complexesmentioning
confidence: 94%
“…[206][207][208][209], have found that, astonishingly, TD-DFT can be in reasonable agreement with the experiment as long as a judicious selection of functionals/basis is done and solvent effects are included. [198,202,206] A recent study on the trans(Cl)-Ru(bpy)Cl 2 (CO) 2 complex shows that functionals bearing intermediate amounts of exact exchange, such as M06, PBE0 and B3LYP, can deliver energies comparable to RASPT2 ones. [210] The question that naturally arises is, which functionals perform better in a particular situation?…”
Section: Excited-state Description Of Transition Metal Complexesmentioning
confidence: 99%
“…The quantities used in the above procedure, spectral and analytical data are given below. Phenyl-1H-1,2,3-triazol-4-yl) 1-(4-Cyanophenyl)-1H-1,2,3-triazol-4-yl]pyridine (4Ia, R = CN [8] General Procedure for the Synthesis of Triazoles 5: A mixture of azide 1C-1E and phenylacetylene 2(f-j,l-n) was cooled to ca. 10°C in an ice-water bath, and CuBr(PPh 3 ) 3 was added to the stirred mixture.…”
Section: General Procedures For the Synthesis Of Triazolesmentioning
confidence: 99%
“…[5] In coordination chemistry, for example, architectures containing this heterocycle have been developed as monodentate and polydentate nitrogen ligands. Special attention has been given to (2-pyridyl)-and more flexible (2-picolyl)-1,2,3-triazoles, [6,7] because they are viewed as surrogates for the well-known 2,2Ј-bipyridine [8] and bis(heterocycle)methane ligands, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…We, and others, have paid particular attention to the use of copper-catalysed coupling of alkynes and azides to form 1,2,3-triazole-based ligands [7][8][9][10] and have investigated the photophysical properties of their resultant complexes. A significant number of reports have appeared detailing the photophysical and photochemical properties of triazole-based complexes of Re(I), Ru(II) and Ir(III) [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Examples of triazole-containing complexes of osmium(II)…”
Section: Introductionmentioning
confidence: 99%